Pre-or postharvest application of putrescine and low temperature storage affect fruit ripening and quality of 'Angelino' plum - Khan, Ahmas; Singh, Zora; Abbasi, Nadeem; Swinny, Ewald (Wiley InterScience, 2008)
BACKGROUND: Plum has a very short storage life. The role of pre- or post-harvest applications of putrescine (PUT) and low temperature storage on fruit ripening and quality was investigated in plum fruit (Prunus salicina Lindl. cv. Angelino).RESULTS: Pre- or post-harvest PUT treatments [(0.1, 1.0 or 2.0 mmol L-1) + 0.01% Tween-20 as a surfactant] delayed and suppressed the climacteric ethylene production and respiration rate irrespective of the method used to apply PUT. PUT-treated fruit following low temperature storage (0 ± 1 °C; 90 ± 5% RH), at the ripe stage exhibited higher fruit firmness and titratable acidity (TA), while soluble solids content (SSC), levels of ascorbic acid, total carotenoids and total antioxidants were lower than in untreated fruit. Fruit both sprayed with PUT and stored in low temperature for 6 weeks, at the ripe stage showed reduced respiration rate, delayed changes in the SSC:TA ratio and levels of total carotenoids compared to post-harvest PUT application.CONCLUSION: Pre-harvest application of 2.0 mmol L-1 PUT 1 week before the anticipated commercial harvest was more effective in delaying plum fruit ripening and can be used to extend the storage (0 ± 1 °C) life of plums for up to 6 weeks with minimum losses in fruit quality. Copyright © 2008 Society of Chemical Industry